Peptide bonds revisited - Santosh Panjikar; Manfred S. Weiss (IUCrJ)
Understanding the structural and chemical properties of peptide bonds within protein secondary structures is vital for elucidating their roles in protein folding, stability and function. This study examines the distinct characteristics of peptide bonds in α-helices and β-strands using a nonredundant data set comprising 1024 high-resolution protein crystal structures from the Protein Data Bank (PDB). The analysis reveals surprising and intriguing insights into bond lengths, angles, dihedral angles, electron-density distributions and hydrogen bonding within α-helices and β-strands. While the respective bond lengths (CN and CO) do not differ much between helices and strands, the bond angles (∠CNCα and ∠OCN) are significantly larger in strands compared with helices. Furthermore, the peptide dihedral angle (ω) in helices clusters around 180° and follows a sharp Gaussian distribution with a standard deviation of 4.1°. In contrast, the distribution of dihedral angles in strands spans a much wider range, with a more flattened Gaussian peak around 180°. This distinct difference in the distribution of dihedral angles reflects the unique structural characteristics of helices and strands, highlighting their respective conformational preferences. Additionally, if the ratio of the electron-density values (2mFo − DFc) at the midpoint of the CO bond and of the CN bond is calculated, a skewed distribution is observed, with the ratio being lower for helices than for strands. Moreover, higher normalized mean atomic displacement parameters (ADPs) for peptide atoms in helices relative to strands suggest increased flexibility or a more dynamic structure within helical regions. Analysis of hydrogen-bond distances between O and N atoms of the main chain reveals larger distances in helices compared with strands, indicative of distinct hydrogen-bonding patterns associated with different secondary structures. All of these observations taken together led us to conclude that peptide bonds in α-helices are different from peptide bonds in β-strands. Overall, α-helical peptide bonds seem to display a more enol-like character. This suggests that peptide oxygen atoms in helices are more likely to be protonated. These findings have several important implications for refining protein structures, particularly in regions susceptible to enol-like transitions or protonation. By recognizing the distinct bond-angle and bond-length variations associated with protonated carbonyl oxygen atoms, current refinement protocols can be adapted to apply more flexible restraints in these regions. This could improve the accuracy of modelling local geometries, where protonation or enol forms lead to subtle structural deviations from the canonical bond parameters typically enforced in refinement strategies.